Feasibility Study of Establishment Plan New Branch of Aksan Motorcycle Repair Shop II in Curahdringu Village Tongas Probolinggo Regency - Aisyah, Synthia Nur; Warsono; Lestari, Novi Puji (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
The purpose of this study is to determine the feasibility of the mitigation plan for the new Aksan Motorcycle Repair Shop II branch. Feasibility is analyzed using five aspects in the feasibility study. The results of the study show that the market and marketing aspects are projected to increase demand and have fulfilled marketing strategies, technical and operational aspects, namely strategic business locations, layout, and selection of technology and equipment that have been adapted to needs. Structuring management and organization that has fulfilled the four management functions. Economic and social aspects have a positive impact on the environment around the project. The financial aspect of PP results is smaller than the project's economic life, the NPV is positive, and the IRR is greater than the required profit level. The conclusion of the research is based on five aspects, this project is worth implementing.